European fixed income markets : money, bond, and interest rate derivatives - Batten, Jonathan; Fetherston, Thomas A.; Szilagyi, Peter G., 1976- (John Wiley, 2004)
The introduction of the euro in 1999 cast a new focus on the financial markets of constituent euro-zone countries, which have subsequently emerged with the second largest bond market in the world. This new book offers in depth insights and advice for any practitioner in the European fixed-income and ancillary derivative markets, and includes in-depth analysis of euro and non-euro markets as well as emerging countries.